ESTUDO DE MÚLTIPLOS CASOS DE PRÁTICAS EDUCOMUNICATIVAS EM ESCOLAS DE SANTA MARIA-RS - Dias, Marcos Pinheiro (2018)
This study presents a study of multiple cases in three educational institutions in the city of Santa Maria, taking into account the mediatization and media devices, technologies, digital social media, network society and studies in education. A qualitative research that uses in its method the study of multiple cases with the main focus of the research developed from the performance of these professionals in educomunicativas activities realizing a detailed survey of each of the cases and strategies and realizing improvements of the use of technological resources education.